1996
DOI: 10.1007/s004410050563
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase-containing neurones and nerve fibres within cardiac ganglia of rat and guinea-pig: an electron-microscopic immunocytochemical study

Abstract: The nitric oxide synthase-immunoreactivity and NADPH-diaphorase activity of intracardiac neurones in the rat and guinea-pig was studied at the ultrastructural level. While some nitric oxide synthase-containing intracardiac neurones were very heavily labelled, with electron-dense immunoprecipitate distributed throughout the neuronal cell bodies and their processes, most of the labelled neurones exhibited a lighter and more patchy distribution of nitric oxide synthase-immunoreactive material. Synapses made by ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Our findings agree with previous data [12,14] on the existence of species-specific peculiarities or cellcell communication mediated by NO and on Ihe ambiguity of NO effect on cells, in pro-titular under pathological conditions.…”
Section: Resultssupporting
confidence: 95%
“…Our findings agree with previous data [12,14] on the existence of species-specific peculiarities or cellcell communication mediated by NO and on Ihe ambiguity of NO effect on cells, in pro-titular under pathological conditions.…”
Section: Resultssupporting
confidence: 95%
“…A similar mechanism may be present in cardiac ganglia. Sosunov et al have shown by immunocytochemical analysis that neurons within cardiac ganglia of the rat and guinea pig contain NOS (38). They further argue, Figure 4.…”
Section: Discussionmentioning
confidence: 94%
“…It is likely that the basal fluorescence signal could originate from a number of sources since NO synthases can be found in endothelial cells (Miethke et al, 2003), neurones and nerve fibres of cardiac ganglia (Sosunov et al, 1996;Sosunov et al, 1995) and subcellularly located within cardiac myocytes e.g. sarcoplasmic reticulum and mitochondria (Xu et , 1999;Kanai et al, 2001).…”
Section: Origins Of Basal No Signalmentioning
confidence: 99%